Healthy cardiac myocytes can decrease sympathetic hyperexcitability in the early stages of hypertension - Davis, Harvey; Liu, Kun; Li, Ni; Li, Dan; Paterson, David J. (Frontiers in Synaptic Neuroscience, 2022)
Sympathetic neurons are powerful drivers of cardiac excitability. In the early stages of hypertension, sympathetic hyperactivity is underpinned by down regulation of M current and increased activity of Cav2.2 that is associated with greater intracellular calcium transients and enhanced neurotransmission. Emerging evidence suggests that retrograde signalling from the myocyte itself can modulate synaptic plasticity. Here we tested the hypothesis that cross culturing healthy myocytes onto diseased stellate neurons could influence sympathetic excitability. We employed neuronal mono-cultures, co-cultures of neonatal ventricular myocytes and sympathetic stellate neurons, and mono-cultures of sympathetic neurons with media conditioned by myocytes from normal (Wistar) and pre-hypertensive (SHR) rats, which have heightened sympathetic responsiveness. Neuronal firing properties were measured by current-clamp as a proxy for neuronal excitability. SHR neurons had a maximum higher firing rate, and reduced rheobase compared to Wistar neurons. There was no difference in firing rate or other biophysical properties in Wistar neurons when they were co-cultured with healthy myocytes. However, the firing rate decreased, phenocopying the Wistar response when either healthy myocytes or media in which healthy myocytes were grown was cross-cultured with SHR neurons. This supports the idea of a paracrine signalling pathway from the healthy myocyte to the diseased neuron, which can act as a modulator of sympathetic excitability.